KEPUASAN PETANI PLASMA TERHADAP PELAYANAN KEMITRAAN DI PTPN XIII PIR V NGABANG - Hendra Hariadi Lumban Batu; Marisi Aritonang; Josua Parulian Hutajulu (Fakultas Pertanian Universitas Tanjungpura, 2022)
Palm oil is one of the commodities that is seeded in Indonesia. It can be seen from the vast oil palm plantations has increased and the production of crude palm oil (CPO) is also increasing, to meet the demand for food and non-food industries. At home, in a span of 14 years from 1990 to 2003 the consumption of palm oil has increased every year, in 1990 the new consumption of 1.2 million tons, in 2003 increased to 3.2 million. The purpose of this study was to determine the Plasma Farmers Satisfaction of Service Partnership in PTPN XIII PIR V Ngabang. The method used daam this study is a survey method of research that is conducted to obtain the factors of the symptoms and seek information from a group or area. The questionnaire uses primary data with respondents numbering 50 people, the variables studied were Smallholders Satisfaction, Reliability (reliability), Tangible (Embodiment / physical evidence), Responsiveness (Seize Power), Assurance (Assurance), Empathy (Empathy). The results of the study are presented in tabular form and are described in the narrative, the result obtained is of 50 respondents regarding the services and materials in the guidance states Unsatisfied 27 respondents (54%), the quality of the means of production is satisfied by 32 respondents (64%), the service factory in TBS less able to accommodate as many as 25 respondents (50%), the core enterprise assistance in tackling pests and diseases of oil palm plantations is satisfied by 25 respondents (50%). Regarding the company's core discipline in obeying the agreement is satisfied by 28 respondents (56%), the core of the company's attitude towards the welfare of farmers not satisfied by 23 respondents (43.40%). Suggestions in this study to provide satisfaction to farmers is expected to the company must provide it in accordance with the wishes of farmers such as providing roads for village farmers routinely provide fertilizer to farmers to increase the production of oil palm fruits.